Diagnóstico da cadeia produtiva da mamona no âmbito do produtor: caso do Ceará - Silva, Vera Lucia da (2009)
The production of biofuels has become an effective way to diversify the world energy matrix, especially with the production of biodiesel, thus contributing to environmental conservation and introducing the possibility of generating income and employment in the field. These facts are of great social and economic impact for the states of the Northeast, in particular, Ceará. The planting of the castor oil plant is a significant alternative to supplement the income of small farmers in Ceará, but the dissemination of this culture needs guidance for the proper management of its prodution chain, highlighting the use of logistics in the various processes of development. As a result of several important aspects, this research focused on the productive chain of the castor oil plant for obtaining biodiesel in the state of Ceará, in the context of the producer. One is the existence of government support, through the Ceará Castor Oil Project, whose objective is to strengthen agribusiness related to the product in the state and to contribute to generating jobs and income in the field. Another is the fact that this is an oilseed crop adapted to the climatic conditions of Ceará from which its byproducts can provide benefits. The objective of this research was to prepare a diagnosis of the productive chain of the castor oil plant of the State of Ceará in the context of the producer. A quantitative study was made using as an instrument a structured questionnaire with 45 questions. The main results of the study, with regard to the socioeconomic aspect of the producers, revealed that the majority (87.0%) are male; 81.9% married; 64,3% with incomes below the minimum wage. As to the parameters of production,the study revealed an average of three years dedication to the planting of the castor oil plant, with average productivity of 202 kg/ha. After the diagnosis, the difficulties encountered by producers in the production chain of the castor oil plant were clearly evident. Revealed is the necessity of implementing a viable logistic structure related to the problem of access to rural credit, processing, storage, marketing and transportation of the product.